Study on the relationship between the degradation degrees of enzymatically extruded glutinous rice and the qualities of fermented Chinese rice wine. (May 2022) - Guan, Zhongjing; Ren, Xiaoru; Bian, Shichao; Xu, Enbo; Jin, Zhengyu; Jiao, Aiquan
Abstract: To help to control the qualities of Chinese rice wine brewed by enzymatically extruded glutinous rice, the correlation between the degradation degrees of extrudates and the qualities of Chinese rice wine were fully studied. Dextrose equivalent (DE), extent of gelatinization (GE), water solubility/absorption index (WSI/WAI), degree of polymerization (DP) distribution and scanning electron microscopy (SEM) of glutinous rice extruded respectively with 0.5‰, 1.0‰, 1.5‰ and 2.0‰ thermostable α-amylase (TS-αA)/mesophilic α-amylase (MS-αA) were determined. Surprisingly, more TS-αA decreased DE value while more MS-αA increased DE value. Both α-amylases reduced WSI with more enzymes. Besides, more TS-αA promoted GE while more MS-αA decreased GE. The contents of DP1, DP3, DP5, DP6, DP7 and other DP fundamentally affected the qualities of Chinese rice wine. DP1 content was significantly negatively correlated with total sugar and amino acid nitrogen, and positively correlated with alcohol degree. The contents of DP3, DP5 and DP6 were significantly positively correlated with amino acid nitrogen, and negatively correlated with alcohol degree. The contents of DP7 and other DP had a very positive correlation with total sugar. It's expected to control the qualities of Chinese rice wine by adjusting the relevant DP's contents. Graphical abstract: Image 1 Highlights: Dextrose content of extrudate was positively correlated with alcohol degree. Water absorption index was extremely positively correlated with dextrose. Extrusion with more mesophilic α-amylase more inhibited gelatinization. Dextrose was not always positively correlated with dextrose equivalent. Dextrose content could be adjusted by extrusion with mesophilic α-amylase.